Nutrient omissions effects on growth, yield, water productivity and profitability of wheat (Triticum aestivum) in maize (Zea mays)-wheat cropping system - JOSHI, EKTA; VYAS, A K; DASS, ANCHAL; DHAR, SHIVA; PRAJAPAT, KAILASH (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted at IARI, New Delhi, India to assess the effect of omitted nutrients on growth, yield and profitability of wheat (Triticum aestivum L.) crop, and to validate the STCR based fertilizer application for targeted yield (5.0 t/ha) of wheat (HD 2967) in maize (Zea mays L.) wheat cropping system. The experiment comprised 15 treatments involving application of N (-PKZn), NP (-KZn), NPK (-Zn) and NPZn (-K) to both maize and wheat crops, to maize and to wheat crop only, absolute control (no nutrient applied), recommended rate of nutrients (150-60-40-5.5 kg/ha N-P-K-Zn) and STCR based application of nutrients (200-75-65-4 kg/ha N-P-K-Zn). The fixed plots experiment was carried out in a three-time replicated randomized complete block design. Growth and yield attributes were influenced by nutrient omission treatments significantly and their values were higher when nutrients were applied based on STCR approach. The STCR-based nutrient application significantly increased dry matter production at harvest and grain yield by 4.2 and 8.4% respectively, over recommended doses of NPKZn. Omission of P and K resulted in 12.4 and 17.5% reduction in grain yield, respectively. The yield reduction was slightly lower with Zn omission (2-5%). The STCR-based NPKZn application resulted in consistently higher gross returns of Rupees 71 658 and Rupees 66 720 and also enhanced water productivity by 9.7 and 7.1% during the year 2012-13 and 2013-14, respectively, compared to balanced fertilization with recommended doses of nutrients. Overall, the results revealed that omitting P and K leads to significant yield penalty and application of nutrients using STCR approach should be adopted for achieving higher yield, water productivity and profitability of wheat.